Comparative gene expression analyses reveal heterochrony for Sox9 expression in the cranial neural crest during marsupial development. Issue 4 (17th June 2014) - Wakamatsu, Yoshio; Nomura, Tadashi; Osumi, Noriko; Suzuki, Kunihiro
SUMMARY Compared to placental mammals, marsupials have short gestation period, and their neonates are relatively immature. Despite these features, marsupial neonates must travel from the birth canal to the teat, suckle and digest milk to complete development. Thus, certain organs and tissues of marsupial neonates, such as forelimbs to crawl and jaw elements to suckle, must develop early. Previous reports showed that cranial neural crest (CNC) cells, as the source of ectomesenchyme of jaw elements, are generated significantly early in gray short‐tailed opossum (Monodelphis domestica) compared to other amniote models, such as mouse. In this study, we examined the expression of genes known to be important for neural crest formation, such as BMP2/BMP4 (neural crest inducer), Pax7 (neural border specifier), Snail1 and Sox9/Sox10 (neural crest specifier) in Monodelphis domestica, and compared the expression patterns with those in mouse, chicken, and gecko embryos. Among those genes, the expression of Sox9 was turned on early and broadly in the premigratory CNC cells, and persisted in the ectomesenchyme of the cranial anlagen in opossum embryos. In contrast, Sox9 expression diminished in the CNC cells of other animals at the early phase of migration. Comparison of the onset of Pax7 and Sox9 expression revealed that Sox9 expression in the prospective CNC was earlier and broader than Pax7 expression in opossum, suggesting that the sequence of border specification and neural crest specification is altered. This study provides the first clue for understanding the molecular basis for the heterochronic development of the CNC cells and jaw elements in marsupials.